PEMANFAATAN SASTRA LOKAL DALAM PENGAJARAN SASTRA - Herawati, Yudianti (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
Teaching literature is deemed not achieve maximum results. Therefore, the teaching of literature needs to be done with the methods and strategies that encourage the achievement level of students' understanding and appreciation of literature adequately. Teaching literature does not only equip students for the knowledge of literature, but rather encourage students to have an understanding of literature in accordance with the function of literature. During this time, the teaching of literature in most schools only happen in the space sandwiched between the classroom walls. The result, the power of imagination and creativity of the students are less developed well. East Kalimantanauthor and work of writers in East Kalimantan is a literary knowledge students should possess at every level of education in schools. Instead, teachers of language and literature not only introduces the literati of Java, Sumatra, or from other islands to the student. In addition, it is no less in the teaching of literature in this province, is the literature regarding the East Kalimantan region. Many teachers of language and literature are less offensive let alone East Kalimantan regional literature. Whereas the East Kalimantan regional literature should be taught once a sufficient proportion in all schools. province.Â